PENGARUH PEMBERIAN MULSA JERAMI PADI DAN PUPUK NPK PHONSKA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG PANJANG (Vigna Sinensis L.) - Nisa, Choirul; Sri Redjeki, Endah; Nur Lailiyah, Wiharyanti (Politeknik Negeri Ketapang, 2023)
Long bean production in Indonesia has decreased accompanied by increased consumer demand, the reason being the lack of intensification of cultivation methods carried out by farmers. The use of mulch and fertilizer can increase crop production. This study aims to determine the growth and yield of long bean plants with different doses of rice straw mulch and Phonska NPK fertilizer. This study used a randomized block design with two factors, the first factor was the dose of mulch (M) and the second factor was the dose of NPK fertilizer (P). These factors were combined into 9 treatments and repeated 3 times to produce 27 experimental units. Data analysis used further variance with the Duncan's Multiple Range Test at a significant level of 5% and the Correlation test. The results showed that there were significant differences in the interaction of rice straw mulch and Phonska NPK fertilizer doses on plant length and number of leaves 4 and 8 weeks after planting. While the variable number of leaves 2 and 4 weeks after planting, leaf area, number of pods, pod weight, fresh and dry weight of stover, and fresh and dry weight of roots did not show any significant interaction.